Hubungan inflasi, minyak dunia, dan sektor transportasi dan logistik - Sendow, Virginia Maria; Pandey, Nansy Joan Francisca (Yayasan Widyantara Nawasena Raharja, 2023)
In addition to impacting world oil prices, global inflation conditions at the beginning of 2023 also triggered changes in the national inflation rate and tended to have an impact on the transportation and logistics index. This study aims to examine the relationship between national inflation, world oil, and transportation and logistics index. This study finds that neither the rate of return of world oil prices nor the national inflation rate has an insignificant relationship with the transportation and logistics index. These results imply that increases or decreases in world oil prices tend not to be followed by fluctuations in the transportation and logistics index. At the same time, these results also imply that changes in the national inflation rate will not be accompanied by changes in the transportation and logistics index.